Systemic risk and the optimal seniority structure of banking liabilities - Bougheas, Spiros; Kirman, Alan (Wiley, 2018)
The paper argues that systemic risk must be taken into account when designing optimal bankruptcy procedures in general, and priority rules in particular. Allowing for endogenous formation of links in the interbank market we show that the optimal policy depends on the distribution of shocks and the severity of fire sales.